I was wrong when I studied Russian nuclear weapons scientists. - Gusterson, Hugh (American Ethnologist, 2025)
Having successfully completed fieldwork in a US nuclear weapons community, I went to Russia to interview a handful of the country's nuclear weapons scientists. Epistemologically, I made the mistake of viewing them more as variant weapons designers rather than as Russians. More seriously, I failed to think through in advance the risks to myself and to my human subjects of interviewing important national security personnel in an (until recently) enemy state where practices of surveillance and arbitrary detention were more salient than in the United States. This partly reflected a broader common sense in anthropology that focuses concern on vulnerable human subjects at the bottom of social structures, not on elites. In subsequent years the digitization of information has at least made it easier to conduct such fieldwork without carrying sensitive data across national borders.